2009
DOI: 10.1103/physrevd.80.084004
|View full text |Cite
|
Sign up to set email alerts
|

Mach’s holographic principle

Abstract: Mach's principle is the concept that inertial frames are determined by matter. We propose and implement a precise formulation of Mach's principle in which matter and geometry are in one-to-one correspondence. Einstein's equations are not modified and no selection principle is applied to their solutions; Mach's principle is realized wholly within Einstein's general theory of relativity. The key insight is the observation that, in addition to bulk matter, one can also add boundary matter. Specification of both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…The latter has very recently become possible even for more complicated theories of gravity, such as DGP or f (R)-gravity (see e.g. Oyaizu 2008; Khoury & Wyman 2009;Schmidt 2009;Li, Zhao & Koyama 2012), such that our method can be fruitfully used to connect such scenarios with observations of galaxies. We plan to expand our present results into this direction in forthcoming work.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…The latter has very recently become possible even for more complicated theories of gravity, such as DGP or f (R)-gravity (see e.g. Oyaizu 2008; Khoury & Wyman 2009;Schmidt 2009;Li, Zhao & Koyama 2012), such that our method can be fruitfully used to connect such scenarios with observations of galaxies. We plan to expand our present results into this direction in forthcoming work.…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…They found that systematic effects could account for at most half of the high dipole moment of the SMAC survey, leaving a dipole moment which is still at least three times higher than the CDM expectation. There are many theoretical possibilities to extend the CDM model to produce a large-scale excess of power and a peculiar velocity dipole, such as modifications to gravity (Ayaita, Weber & Wetterich 2009;Khoury & Wyman 2009), dark energy clustering (Potter & Chongchitnan 2011), vorticity (Palle 2010) or 'tilted' universes (Mersini-Houghton & Holman 2009Kashlinsky et al 2010;Ma et al 2011). In this work, we do not address any theoretical explanation in particular, but by using the peculiar velocity data to constrain the power spectrum in model-independent band powers, we aim to provide results which will be useful to constrain a range of explanations for the high dipole.…”
Section: Introduction a N D Bac K G Ro U N Dmentioning
confidence: 99%
“…If modifications to gravity are included, however, then one has to make an assessment of how well large-scale structure growth in the non-linear regime is understood. Recent analyses show that in some specific MG theories there can be subtleties in the non-linear behaviour that might have to be included (Oyaizu 2008;Oyaizu, Lima & Hu 2008;Khoury & Wyman 2009;Figure 5. The impact of the number of k and z bins, N k = N z = N bias , in the bias model on the EoS parameter and MG FoMs.…”
Section: Surveymentioning
confidence: 99%